Historical medium-scale maps as a source of information on the overgrowing of lakes - Ptak Mariusz (Limnological Review, 2013)
In the work, medium-scale topographic maps from the first half of the 20th century and aerial photographs from the first decade of the 21st century were used to determine the rate of overgrowing of lakes. A comparison of results for lakes located in different parts of Poland demonstrated that the process of proliferation of emergent plants dominated - such a situation was recorded for 14 out of the 15 lakes analysed in the work. The calculated average overgrowing rate for all the lakes in the years 1945-2010 was 0.4 ha yr-1. Lake Karaś (1.83 ha yr-1) and Lake Oświn (1.2 ha yr-1) were characterized by the highest overgrowing rates. Moreover, the work presents an attempt at discovering the factors which determine the scale of the lake overgrowing process. To this end, the main lake parameters were analysed and it was concluded that the rate of overgrowing of lakes was influenced, inter alia, by water level fluctuations and the shape and depth of a given lake. However, each lake should be treated as an individual object which responds to the processes occurring in its environment in a unique way.